PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA KARYAWAN - Fahrina Amalia; Gde Bayu Surya Parwita; Ni Nyoman Suryani (Forum Manajemen STIMI Handayani Denpasar, 2019)
Job satisfaction is important and needs to be considered by every company, because Human Resources is the main factor and actor in the work process. The low job satisfaction of employees in a company is a symptom of the less stable the company. Employee dissatisfaction in work can be due to individual characteristics or behavior of the employees themselves who have not been in accordance with what is expected of the company and understanding of karkateristik work either by employees or companies are still low. The purpose of this study is to determine the effect of individual characteristics and job characteristics on employee job satisfaction either simultaneously or partially. The method used in this research is descriptive method with quantitative approach. The population of this study amounted to 56 with saturated sampling technique / census. Methods of data analysis using multiple linear regression analysis using SPSS version 23.0 for windows. The results showed that the characteristics of individual employees into the category of good, so it is with employee job characteristics and employee job satisfaction. Individual characteristics and job characteristics have a strong correlation with employee job satisfaction and simultaneously and partially have a significant effect on job satisfaction. The magnitude of the influence of both variables is equal to 71.8% and partially individual characteristics have a relatively higher influence compared with job characteristics to job satisfaction.